2022
DOI: 10.1126/science.abn8289
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing noble metal utilization in solid catalysts by control of nanoparticle location

Abstract: Maximizing the utilization of noble metals is crucial for applications such as catalysis. We found that the minimum loading of platinum for optimal performance in the hydroconversion of n -alkanes for industrially relevant bifunctional catalysts could be reduced by a factor of 10 or more through the rational arranging of functional sites at the nanoscale. Intentionally depositing traces of platinum nanoparticles on the alumina binder or the outer surface of zeolite crystals, instead of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 42 publications
1
79
0
Order By: Relevance
“…Additionally, the synthesis method, e.g., direct inclusion of magnesium in the synthesis gel or ion exchange, could also have a large effect on the final magnesium distribution as well on the bulk-nanoscale coking behavior. The distribution of Mg (and other metals) could have a drastic effect on the final catalytic performance, which would require further comparison studies between samples with different metal distributions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the synthesis method, e.g., direct inclusion of magnesium in the synthesis gel or ion exchange, could also have a large effect on the final magnesium distribution as well on the bulk-nanoscale coking behavior. The distribution of Mg (and other metals) could have a drastic effect on the final catalytic performance, which would require further comparison studies between samples with different metal distributions …”
Section: Resultsmentioning
confidence: 99%
“…The distribution of Mg (and other metals) could have a drastic effect on the final catalytic performance, which would require further comparison studies between samples with different metal distributions. 52 ■ CONCLUSIONS Zeolite SSZ-13 was successfully modified with magnesium via an impregnation preparation step. With atom probe tomography (APT), it was discovered that magnesium is heterogeneously distributed through the sample and tends to aggregate on the nanoscale, unlike the framework elements of the zeolite.…”
Section: Nanoscale Coking Behaviormentioning
confidence: 99%
“…This fact has been recently proved in the hydroconversion of n-alkanes towards branched hydrocarbons over Pt/HZSM-22/Al 2 O 3 catalysts. 38 In a previous study, we reported that the tandem catalytic system RANEY® Ni plus nanocrystalline or hierarchical ZSM-5 39 unveiled alkylation reactions in the phenol conversion alongside the expected reactions (ring saturation, dehydrogenation and dehydration). This alkylation shifted the selectivity towards bulky alkylphenolic products, cresols and cyclo-hexylphenols being the main ones obtained (36% and 17% selectivity respectively over RANEY® Nickel plus hierarchical ZSM-5 at 175 °C).…”
Section: Introductionmentioning
confidence: 94%
“…This fact has been recently proved in the hydroconversion of n -alkanes towards branched hydrocarbons over Pt/HZSM-22/Al 2 O 3 catalysts. 38…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic activity was improved further by the hybridization of Pt nanoparticles as reported for other semiconductor photocatalysts. 5,32 The intercalation of [Pt(NH 3 ) 4 ] 2+ as the Pt precursor to Fe-clay and subsequent photoreduction were performed leading to the deposition of Pt nanoparticles on Fe-clay during the photocatalytic reaction. Although the preparation of Pt nanoparticles on clay minerals has been reported by chemical/thermal reduction (Table S5, ESI †), photoreduction has not been used so far.…”
mentioning
confidence: 99%